INVESTIGATION OF A HYBRID REDUNDANCY IN THE FAULTTOLERANT SYSTEMS - Tyurin, S. F. (Radio Electronics, Computer Science, Control, 2019)
Context. Structural redundancy is one of the main ways to create highly reliable devices and systems for critical applications. The object of the study was hybrid redundancy in the Fault-Tolerant Systems, for example in aerospace hardware exposed to radiation. Objective. The goal of the work is the calculation of the complexity and probability of failure-free operation of digital circuits with hybrid redundancy combining tripling, deep tripling, and quadding. The comparison shows that tripling is not always better than a circuit without redundancy over a sufficiently large time interval. Good results are obtained by tripling with three majority voters and deep tripling, but the latter significantly increases the time delay of the signal. The greatest gain in reliability provides quadding at the transistors level, but it is not always possible due to the restrictions of Mead-Conway, in addition, the delay at least is doubled. The article describes proposed method of the combined redundancy taking into account the necessary hardware costs and time delay. Method. Determining the complexity in the units of the conditional number of transistors and maximum signal path from the input to the output in the number of transistors, as well as using the Weibull distribution to estimate the probability of failure-free operation. Simulation of proposed hybrid redundancy in the system NI Multisim by National Instruments Electronics Workbench Group. The failure-free operation probability estimation in the computer mathematics system MathCad. Results. Expressions are obtained for the estimates of complexity, time delay and probability of failure-free operation of redundant digital circuits; curves are built in the Mathcad. Simulation confirms the performance of the proposed redundancy options. Conclusions. The conducted studies allowed us to establish the effectiveness of hybrid redundancy to improve the reliability and the radiation resistance of the digital circuits.